El fortalecimiento de la competencia comunicativa oral y el pensamiento crítico a través del debate como estrategia pedagógica en estudiantes de grado décimo de la IED liceo femenino Mercedes Nariño. (2023)
The purpose of this research is to strengthen oral communicative competence through debate as a pedagogical strategy at the liceo femenino Mercedes Nariño school, in this way it is intended to respond to various objectives that go hand in hand with the development and critical analysis of classical literature taken to modern context to generate critical positions in the students of the tenth grade from perspectives such as those of Jurado (2018), Lomas (1999), Luna (1994), Cassany (2006) and Cestero (1999), a work is proposed from the research-action Alvarez (2014) and Latorre (1998). Thus, developing a line of qualitative action-research with four phases that seek to question social practices in order to intervene and transform them progressively in various phases of planning, action, observation and reflection, the 4 phases to be developed are 1. Delimitation of the problem to be investigated in action, 2. Planning the action process, 3. Thus, the development of a proposal that allows to demonstrate how oral communicative competence can be strengthened through debate as a pedagogical strategy and the assertive analysis of classical literature.